2021
DOI: 10.1186/s13634-020-00714-2
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate tracking in photoplethysmography signals affected by motion artifacts: a review

Abstract: Non-invasive photoplethysmography (PPG) technology was developed to track heart rate during motion. Automated analysis of PPG has made it useful in both clinical and non-clinical applications. However, PPG-based heart rate tracking is a challenging problem due to motion artifacts (MAs) which are main contributors towards signal degradation as they mask the location of heart rate peak in the spectra. A practical analysis system must have good performance in MA removal as well as in tracking. In this article, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 97 publications
0
42
0
Order By: Relevance
“…Since modern wearable applications demand for these measures, this research concentrates on HR tracking algorithms applied in time domain. Before the pulse feature detection and validation takes place, usually preprocessing and motion artifact removal stages are applied [19], [40].…”
Section: A Methods For Heart Rate Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Since modern wearable applications demand for these measures, this research concentrates on HR tracking algorithms applied in time domain. Before the pulse feature detection and validation takes place, usually preprocessing and motion artifact removal stages are applied [19], [40].…”
Section: A Methods For Heart Rate Monitoringmentioning
confidence: 99%
“…Consequently, the universal cardiac and respiratory frequency bands, for both infants and adults, overlap. The separation of the desired signal components from in-band noise, especially motion artifacts from daily activities such as walking and jogging (1.0 to 2.5 Hz), becomes even more challenging [18], [40].…”
Section: A Methods For Heart Rate Monitoringmentioning
confidence: 99%
“…Due to the high probability of the proximity of HR and motion artifact spectral peaks and spectral peak randomness, the removal of motion artifacts is an important preprocessing step in classical signal processing to calculate the HR from PPG. In [19], HR calculations were divided into four phases, including pre-filtering, motion artifact removal, peak detection, and peak tracking. Zong [20] addressed the HR tracking problem in two distinct stages: pre-filtering and peak tracking.…”
Section: Sources Of Inaccuracy-motion Artifactsmentioning
confidence: 99%
“…Ismail [19] showed that the Laplacian model exhibited the best fit for analyzing the d process. Based on the analytical results, the probability density function ( ) is given by the following:…”
Section: Laplacian Distributionmentioning
confidence: 99%
“…The periodicity of measured light corresponds to the cardiac rhythm, which is used for HR estimation [ 6 ]. However, this method has one major drawback: during intense physical activity, the PPG signal is very susceptible to interference [ 7 ]. Reducing the influence of motion artifacts is currently a leading research direction in HR estimation.…”
Section: Introductionmentioning
confidence: 99%